Childhood growth prior to screen-detected celiac disease: prospective follow-up of an at-risk birth cohort. (1st November 2020) - Stahl, Marisa G.; Dong, Fran; Lamb, Molly M.; Waugh, Kathleen C.; Taki, Iman; Størdal, Ketil; Stene, Lars C.; Rewers, Marian J.; Liu, Edwin; Norris, Jill M.; Mårild, Karl
Abstract: Objectives: To determine the association between childhood growth prior to the development of celiac disease (CD) and CD autoimmunity (CDA) identified by periodic serological screening. Study design: The Diabetes Autoimmunity Study in the Young cohort includes 1979 genetically at-risk children from Denver, Colorado, with annual growth measurements from age nine months until ten years. Between 1993 and February 2019, 120 children developed CDA defined by persistent positive tissue transglutaminase autoantibodies (TGA); among these, 71 met our criteria for CD based on histopathological findings or high TGA levels. Age- and sex-specific z -scores of weight, body mass index (BMI), and height prior to seroconversion were derived using US reference charts as standards. Joint modeling of serial growth measurements was used to estimate adjusted hazard ratios (aHRs) accounting for celiac-associated human leukocyte antigens, early-life feeding practices, and socio-demographics. Results: In the first 10 years of life, there were no significant associations between the child's current weight, BMI and height and the risk of screening-detected CDA or CD, neither was the weight nor BMI velocity associated with CDA or CD as identified by screening (all aHRs approximated 1). Increased height velocity was associated with later CD, but not CDA, development (aHR per 0.01- z score/year, 1.28; 95% confidence interval [CI] 1.18–1.38 and 1.03; 0.97–1.09, respectively). Conclusions: In the first 10 years of life, from prospectively collected serial growth measurements, we found no evidence of impaired childhood growth before CD and CDA development as identified through early and periodic screening.